Price Based on Islamic Law Perspective - Hilal, Syamsul (International Journal of Psychosocial Rehabilitation, 2020)
Some factors that trigger for the price fluctuation can be grouped into two factors, namely external factors related to the producer and distribution of commodity trade goods in order to do business with fair play and avoid corruptive and manipulatives behavior. While the internal factor is an opportunistic of consumer behavior in buying commodities trade goods so as not to obtain a competitive price. The addition of the sale price of sharia institutional financing services is permissible considering the payment pattern due to tempo and installment requires long time tenor service that requires operational cost and proportional profit. Trading activities essentially require a fairness in the field of price. The trade war and the dumping behavior of the international trading world are gaining a competitive price from its trade commodity. Fuqahā’ which is a group of Islamic law thinkers makes methodological parameters and legal parameters related to the price and the dynamics of the problem as a reference to the Islamic economic attitudes of the Muslims in order not to get stuck on Ribawi transactions.